Enhancing drivers’ situation awareness - Gregoriades, Andreas; Pampaka, Maria (My University, 2017)
This work describes the evaluation of a prospective situation awareness enhancement system (SAES) that exploits augmented reality through a head up display. The specification of the proposed SAES is based on domain knowledge from the literature. Herein, a method is described that utilizes the benefits of a modular simulator to model the design of a prospective SAES. The situation awareness assessment method used is based on the Situation awareness global assessment technique (SAGAT) and utilizes data obtained from the simulator that replicates the infrastructure of a road network in Cyprus. The simulator mimics the functionality of a prototype SAES using a number of candidate visualization metaphors, that simulate a number of candidate head up display designs. The paper describes the process of assessing the situation awareness of drivers that use a prototype smart SAES, through a series of experiments in a virtual reality CAVE. The effectiveness of the SAES is tested in a between-groups research design.
Keywords: SAGAT; Situation awareness; Situation awareness enhancement system